2021
DOI: 10.1016/j.radcr.2021.05.039
|View full text |Cite
|
Sign up to set email alerts
|

A case of eosinophilic gastroenteritis with high PET-CT accumulation treated by P-CAB

Abstract: Eosinophilic gastroenteritis (EGE) can present findings on computed tomography (CT) images that resemble malignant tumors. EGE is generally treated with systemic oral steroid administration, which is reportedly effective in relieving symptoms at least temporarily. Here, we report a case of EGE that mimicked malignant lymphoma in a gastroduodenal lesion, in which treatment with a potassium-competitive acid blocker without systemic oral steroid administration relieved the symptoms and reversed the initial image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Subsequently, in combination with the histopathology of further EUS-guided FNA, history of present illness and laboratory examination, and importantly, a favorable response to steroid therapy, we nally diagnosed that this patient had the HES prominently involving the stomach. Herein, we searched previous literatures around the situation of eosinophilic in ltration-simulated tumors, and found that they have once been misdiagnosed or suspected as lymphoma in distal stomach and duodenum, colon cancer with hepatic metastases, pancreatic tumor, and late-stage gastric carcinoma [10][11][12][13][14]. We summarized the characteristics of these cases involving digestive system in the Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in combination with the histopathology of further EUS-guided FNA, history of present illness and laboratory examination, and importantly, a favorable response to steroid therapy, we nally diagnosed that this patient had the HES prominently involving the stomach. Herein, we searched previous literatures around the situation of eosinophilic in ltration-simulated tumors, and found that they have once been misdiagnosed or suspected as lymphoma in distal stomach and duodenum, colon cancer with hepatic metastases, pancreatic tumor, and late-stage gastric carcinoma [10][11][12][13][14]. We summarized the characteristics of these cases involving digestive system in the Table 1.…”
Section: Discussionmentioning
confidence: 99%